Parasitic Architecture: Developing a Thematic Design Framework for Adaptive Reuse as an Urban Regeneration Strategy in Kuala Lumpur, Malaysia - Manan, Mohd. Shahrudin Abd.; Yuan, Yap Zhen (MAJ - Malaysia Architectural Journal, 2025)
Parasitic architecture embodies an innovative design approach that reconceptualises existing structures as the foundation for new construction endeavours. This approach presents a progressive and adaptive alternative for urban regeneration, adeptly addressing issues like urban decay and overdevelopment. Despite the increasing global recognition of parasitic architecture, Malaysia nevertheless remains heavily dependent on inefficient and unsustainable building demolition practices. The practices have led to the destruction of significant historical edifices and the abandonment of numerous dilapidated structures, resulting in a dissonance between old and new developments in urban regeneration efforts. Against this backdrop, this article aims to propose a design framework that appropriates parasitic architecture as an adaptive reuse strategy for the urban regeneration process. The proposition is posited within the context of assimilating parasitic architecture into the urban fabric of Malaysia, particularly focusing on the metropolis of Kuala Lumpur. To attain this, the article first explores the theoretical underpinnings and design constraints of parasitic architecture, followed by expert interviews with six experienced practitioners to gather first-hand opinions and comprehensive insights. The findings lay the groundwork for a thematic-based design framework, which posits a sustainable approach for repurposing existing structures while safeguarding their environmental and historical cultural significance. This investigation into parasitic architecture, as an exploratory thematic study, would pave the way for more design research possibilities. It could benefit relevant stakeholders, including local authorities, architects, designers, planners, and researchers alike, in expanding the urban regeneration paradigm.